IMPLEMENTASI MANAJEMEN KUALITAS DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN PDAM LOMBOK TENGAH - L. WIRAHMAN W; I GEDE PUTU WARKA; I.A.O SUWATI SIDEMAN (GANEC SWARA, 2020)
Drinking water is one of human’s primary needs that must be fulfilled in term of quantity and quality. PDAM Lombok Tengah is a local company that provided the drinking water service for all 12 districts in central Lombok. Praya City is the biggest area of service that coverage 71,83% of costumers of PDAM Lombok Tengah. Therefore this area should be given the most concern in term of services quality. Complains that have been sent by costumers towards PDAM Lombok Tengah is indicating the dissatisfaction in services. PDAM Lombok Tengah must be able to examine the conditions and phenomena in the community related to factors that affect the satisfaction of its customers, and then respond with the implementation of adequate quality management. According to the research that has been done the highest average score of quality management implementation rate is 75,88%, this score is implied by using and communicating costumers information. The Satisfaction rate of domestic costumers of PDAM Lombok Tengah in Praya City is shown to be satisfied enough with average rate of 64,167%. This rate is influenced by water quality, water continuity, water pressure, water’s meter condition, maintenance, billing and payment system, services cost, and water quality